Study on the noise and vibration of engine block coupled with the rotating crankshaft and gear train (Effect of the torsional vibration of crankshaft) - Kazuhide OHTA (The Japan Society of Mechanical Engineers, 2014)
As the small-sized high speed diesel engine used for construction machinery and generator is operated under continuous heavy load condition, a gear train is employed to drive the fuel injection pump and valve train. When a loading torque is small at the idling condition, the gear tooth separation and impact are caused by the fluctuating torque and they increase the engine noise level. Particularly when the torsional vibration of the crankshaft occurs and its rotational amplitude is magnified at a specified rotational speed, the gear impact is intensified and it leads to increase of engine noise. Author has developed the theoretical procedure using FEM, modal analysis technique and BEM to predict the vibratory response and radiated noise of the engine block coupled with the rotating crankshaft and gear train shafts which drives the fuel injection pump and valve system. This method is applied to reveal the effect of torsional vibration of crankshaft on the gear impact force and engine noise of the four-stroke four-cylinder engine. Countermeasure to reduce vibration and noise by changing the location of the gear train from pulley side to flywheel side of the crankshaft is evaluated and its result indicates the prospects which can reduce the radiated noise from the engine block.